Serum Macro-Minerals Profile and Conception Rate following Heatsynch and Heatsynch + PRID Protocols in Subestrus Surti Buffaloes - Saxena, Swati; Khasatiya, CT; Savani, HR; Patel, SB; Chaudhary, SS (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
A study was carried out to interpret the first and second service conception rate along with serum macro-minerals profile for Heatsynch (T1) and Heatsynch + PRID (T2) protocols with fix timed AI in subestrus Surti buffaloes (n=6 each), keeping one group as untreated control (T3). In Heatsynch protocol, buffaloes were administered i.m. with Inj. Busereline acetate 10 µg on day 0, Inj. Cloprostenol sodium 500 μg on day 7 and Inj. oestradiol benzoate (EB) 0.5 mg on day 8 followed by FTAIs twice on day 10, while in Heatsynch + PRID protocol the buffaloes were inserted with PRID (0.96 g of progesterone) intravaginally for 7 days together with above Heatsynch protocol. Blood samples were collected aseptically in vaccutainers from all these animals on day 0 (prior to treatment), day 4 (during treatment), day 8 (after PGF2α inj.), day of induced estrus/FTAI and on day 28 (post-treatment, day 18 post-AI), and serum samples were stored at –20°C until analyzed. The buffaloes that became pregnant at 1st service (FTAI) in the treatment group T1 & T2 were 50.00 (3/6) and 66.66 (4/6) % and at 2nd cycle 100.00 (3/3) and 50.00 (1/2) %, respectively. The corresponding conception rates for control group T3 were 33.33 (2/6) and 50.00 (2/4) %. The overall pooled CRs of 2 cycles achieved in groups T1, T2 and T3 were 100.00 (6/6), 83.33 (5/6) and 66.66 (4/6) %, respectively. The overall mean serum calcium, phosphorus and magnesium values did not differ significantly (p>0.05) among T1, T2 and T3 groups at any day or within group between different sampling intervals. Heatsynch alone was better and economic over other groups in managing subestrus buffaloes.